The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1021/acs.jmedchem.9b01294
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Chlorin/Arylaminoquinazoline Conjugate for Photodynamic and Targeted Therapy

Abstract: A new water-soluble conjugate, consisting of a chlorin-e 6 photosensitizer part, a 4-arylaminoquinazoline moiety with affinity to epidermal growth factor receptors, and a hydrophilic β-D-maltose fragment, was synthesized starting from methylpheophorbide-a in seven steps. The prepared conjugate exhibited low levels of dark cytotoxicity and pronounced photoinduced cytotoxicity at submicromolar concentrations in vitro, with an IC 50 (dark)/IC 50 (light) ratio of ∼368 and a singlet oxygen quantum yield of about 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 59 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…However, 194a and 194b showed similar and high photocytotoxicity in several cancer cell lines, indicating the vital role of glycoconjugation in the PDT efficiency of these PSs. In another approach with metalated PS, Fedorov et al reported a water-soluble arylaminoquinazoline–Zn­(II) chlorin conjugate ( 195 ) for targeted PDT ( 195b ) . 4-Arylaminoquinazolines have a high affinity for EGFRs, and the hydrophilic β- d -maltose fragment acts as a hydrophilic group.…”
Section: Representative Strategies For Conventional Photosensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 194a and 194b showed similar and high photocytotoxicity in several cancer cell lines, indicating the vital role of glycoconjugation in the PDT efficiency of these PSs. In another approach with metalated PS, Fedorov et al reported a water-soluble arylaminoquinazoline–Zn­(II) chlorin conjugate ( 195 ) for targeted PDT ( 195b ) . 4-Arylaminoquinazolines have a high affinity for EGFRs, and the hydrophilic β- d -maltose fragment acts as a hydrophilic group.…”
Section: Representative Strategies For Conventional Photosensitizersmentioning
confidence: 99%
“…In another approach with metalated PS, Fedorov et al reported a water-soluble arylaminoquinazoline−Zn(II) chlorin conjugate (195) for targeted PDT (195b). 381 3.2.2. Chlorin e 6 .…”
Section: Chlorin Derivativesmentioning
confidence: 99%
“…Furthermore, the excessive lipophilicity of these photoactive compounds results in dark toxicity due to aggregation in biological liquids. 13 Some water-soluble derivatives of second-generation PSs are available, although natural compounds with polar side chains are a better alternative. To summarize, an ideal PS should have (i) high chemical purity, (ii) easy synthetic routes, (iii) high photochemical reactivity, (iv) good aqueous solubility and tissue penetration, and (v) excellent biocompatibility.…”
mentioning
confidence: 99%
“…Several research groups have designed and synthesized smart PSs with optimized therapeutic efficacy, such as porphyrin, chlorin, and phthalocyanine derivatives. The first-generation PS photofrin is widely used in clinical applications despite its low chemical purity (it is a mixture of over 60 molecules), poor tissue penetration (due to absorption of short wavelength at ∼630 nm), and low clearance rates. , The second-generation PSs like benzoporphyrin derivatives, thiopurine derivatives, and phthalocyanines are characterized by higher chemical purity, longer T1 lifetime, higher yields of 1 O 2 and stronger absorption in the red region of the spectrum. , However, the second-generation PSs still have considerable drawbacks such as poor aqueous solubility, poor fluorescence emission and ROS generation, and adjuvant dissolution before administration. Furthermore, the excessive lipophilicity of these photoactive compounds results in dark toxicity due to aggregation in biological liquids . Some water-soluble derivatives of second-generation PSs are available, although natural compounds with polar side chains are a better alternative.…”
mentioning
confidence: 99%
“…These results strongly suggest that the Warburg effecta phenomenon where tumors consume higher Glc levels than normal cellscan be utilized in the conception to develop the third-generation PS. Naturally occurring chlorin derivatives are also targeted for glycoconjugation. Recently, chlorin e6 (Ce6) has been decorated with Glc to develop a new family of PS (Glc–Ce6), which shows an extremely high photocytotoxicity. , Ce6 is a molecule that is derived from naturally occurring chlorophyll a ; therefore, G–Ce6 is expected to show an improved biocompatibility and body clearance, meeting the requirements of both (d) no toxicity in the dark and (e) rapid clearance out of the body after the treatment. However, as a matter of fact, G–Ce6 is insoluble in water due to the strong hydrophobic property of the Ce6 unit.…”
Section: Introductionmentioning
confidence: 99%